The intrusive hyphen is everywhere: Is seemingly indiscriminate hyphen use symptomatic of current language change?. Issue 4 (December 2019) - Booth, John E.
Abstract : When can a hyphen be described as 'intrusive'? As with many other 'rules' of grammar and of punctuation, use of the hyphen is limited to a specific syntactical context. Hence, to use a hyphen where it should not be used makes it intrusive. Just like the apostrophe, it cannot be used arbitrarily. There is, for instance, a tattooist parlour in the English town of Oldham whose shopfront advertises Inkcredible Tatoo's (sic) and, with it, both the owner's or owners' ability to play on words in writing and their inability to sign a plural form correctly – the rule being that apostrophes are not used to mark the plural of either common or proper nouns in written English.